Pengaruh Tuntutan Kerja dengan Moderasi Panggilan Kerja saat Work From Home terhadap Work Engagement pada Guru - Timotius Setyono; I Nyoman Sutapa (Jurnal Titra, 2021)
Education is important because we will never stop learning both formally and informally. This is also supported by the government in Article 34, paragraphs (1) and (2) of Law no. 20 of 2003 concerning the National Education System. However, the government program cannot run without the role of the teacher because the teacher is not only tasked with teaching, but also to guide, train, etc. Therefore, it is important for teachers to have work engagement in order to carry out their work well. Especially during a pandemic, where there are changes in teaching procedures that require teachers to adapt and work extra to prepare teaching needs. With the increasing demands of work, gradually this will affect the work engagement of teachers. Therefore, it is important for teachers to have a calling, so that they consider that what they are doing is a service or dedication.